A cryptic complex of Transversotrema species (Digenea: Transversotrematidae) on labroid, haemulid and lethrinid fishes in the Indo–West Pacific Region, including the description of three new species - Hunter, J. A.; Ingram, E.; Adlard, R. D.; Bray, R. A.; Cribb, T. H. (Zootaxa, 2010)
Sequences of ITS2 rDNA of 36 individuals of 16 host/parasite/location combinations of transversotrematids from labrid, scarid, haemulid and lethrinid fishes from Heron and Lizard Islands on the Great Barrier Reef and Ningaloo Reef Western off Australia comprised four distinct genotypes. One genotype was associated with three species of Labridae at Heron Island, the second with eight species of Scaridae at Heron Island, the third with two species of Scaridae from Ningaloo, and the fourth with two species of Lethrinidae and one of Haemulidae from Lizard Island. All four forms are broadly morphologically similar to Transversotrema haasi Witenberg, 1944. The two genotypes from scarids differed at only a single base position and were morphologically indistinguishable; all other combinations of genotypes differed by at least 3 bases. Comparisons between specimens from labrids, scarids, and haemulids and lethrinids revealed consistent differences in the number of vitelline follicles enclosed by the cyclocoel and in the relative sizes of the testes. We conclude that these three forms should be considered distinct species. The species associated with labrids is broadly consistent with and has previously been identified as T. haasi which was originally reported from an unknown fish from the Red Sea. As no molecular comparison can be made between the original T. haasi and the three similar forms from Australia, we propose three new species: Transversotrema elegans n. sp. from labrids, T. gigantica n. sp. from scarids, and T. lacerta n. sp. from haemulids and lethrinids.